(untitled) (Research, Society and Development, 2025)
This work aims to help teachers understand and apply assessment that contributes to students’ meaningful learning. A qualitative bibliographical study and a narrative literature review were conducted. The aim is to educate citizens aware of their importance in building a more just and democratic society; to differentiate exams from an effective assessment of school learning; to identify the main problems of traditional classificatory assessment; to understand the necessity of grade records in assessment; to study the concepts and applicability of diagnostic and formative assessment; and to understand that the main objective of assessment is meaningful learning. The importance of the teacher’s role as a mediator in the teaching and learning process is also emphasized. Another objective is to understand and understand the applicability of learning strategies and instruments used in innovative assessment and the importance of student self-regulation of learning. Assessment is understood as continuous and learning recovery parallels the teaching process; and the teacher must guide and facilitate necessary recovery actions.